Full Genome Analysis of Influenza A(H1N1)pdm09 Virus Isolated from Peru, 2013 - Carlos Padilla; Fredy J Condori; Maribel Huaringa; Pool Marcos-Carbajal; Nancy Rojas; Victoria Gutiérrez; Omar Cáceres (My University, 2014)
The pandemic influenza A(H1N1)pdm09 virus has been reported in Peru since 2009. We report the whole-genome sequence analysis of a viral isolate from an infection case that occurred during an influenza outbreak in 2013. This strain shows novel hemagglutinin (HA) mutations that may cause an antigenic drift that diminishes the protective effect of the vaccine.
Keywords: Virology; Biology; Outbreak; Hemagglutinin (influenza); Antigenic shift; Virus; Genome; Strain (injury); Pandemic; Whole genome sequencing; Antigenic drift; H5N1 genetic structure; Influenza A virus; Genetics; Gene; Coronavirus disease 2019 (COVID-19); Medicine; Infectious disease (medical specialty); Disease; Anatomy; Pathology; Virology; Biology; Outbreak; Hemagglutinin (influenza); Antigenic shift; Virus; Genome; Strain (injury); Pandemic; Whole genome sequencing; Antigenic drift; H5N1 genetic structure; Influenza A virus; Genetics; Gene; Coronavirus disease 2019 (COVID-19); Medicine; Infectious disease (medical specialty); Disease; Health Sciences Medicine Epidemiology Influenza Virus Research Studies; Health Sciences Medicine Epidemiology Respiratory viral infections research; Life Sciences Biochemistry, Genetics and Molecular Biology Molecular Biology RNA and protein synthesis mechanisms